REKRUTMEN PARTAI GERAKAN INDONESIA RAYA DALAM KETERWAKILAN PEREMPUAN DI DPRD KOTA PEKANBARU TAHUN 2024. - Hamzen, Imelda Purnama Dinda; ,, Ishak (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
This research refers to Law Number 2 of 2011 on Political Parties and Law Number 7 of 2017 on General Elections for the People's Representative Council (DPR), the Regional Representative Council (DPD), and the Regional People's Representative Council (DPRD). However, in practice, the political rights equality between men and women still needs to be improved. This is evident in the Great Indonesia Movement Party (Gerindra) in Pekanbaru, which, despite having many female cadres, has only one female representative in the Pekanbaru City DPRD in 2024, who comes from the Gerindra Party faction. This research method uses a qualitative approach with data collection techniques in the form of interviews, documentation studies, and literature reviews. The data analysis technique used is descriptive analysis. This study uses the theory of the model of recruitment by Pippa Norris and internal and external factors by Drude Dahlerup, to analyze the representation of women in the Great Indonesia Movement Party in the Pekanbaru City DPRD in 2024. The results of the study indicate that, through the analysis of the recruitment model, it is implemented openly and democratically in accordance with the applicable legal system. In addition, by considering internal factors, the Great Indonesia Movement Political Party (Gerindra) has conducted political education and cadre meetings. However, some political activities carried out tend to be general in nature and have not focused enough on increasing women's representation in the Pekanbaru City DPRD. External factors also show that prospective legislative candidates experience obstacles and challenges, especially in terms of forming a successful team. This is a challenge for the Gerindra Party to measure the electoral potential of female candidates who are not yet optimal in showing initiative and ability to build external support in fulfilling women's representation in the Pekanbaru City DPRD. Keywords : Political Recruitment, Women's Representation, and General Elections